Análise comparativa da presença de patógenos bucais em dois esquemas de reabilitação oral sobre implantes - Matos, Daniella Andaluza Dias (2005)
The interface (microgap) between the implant and abutment can facilitate the plaque accumulation and bacterial proliferation as well as can cause crestal bone changes around titanium implants. The purpose of this study was to identify qualitative differences between the microbiotas of implants with 2 - piece configuration (Brånemark Protocol - group 1) and 1 - piece implants (Novum System-group 2). Twenty patients divided in these two groups (2 - piece configuration and 1 - piece implants) were evaluated and had their peri-implantar sub gingival bacterial plaque collected and analyzed by means of Polimerase Chain Reaction (PCR), which is a relatively new method for evaluation based on the analysis of nucleic acids and presents high sensitivity and fast completion, to identify some of the most important microorganisms involved in the peri-implantar disease like Actinobacillus actinomycetemcomitans, Porphyromonas gingivalis and Prevotella intermedia. Regarding the values for the group 1 (34 samples), the microbiota comprised 85,29% (29 samples) of Actinobacillus actinomycetemcomitans, only 14,71% (5 samples) of Porphyromonas gingivalis and 11,77% (4 samples) of Prevotella intermedia and for the group 2 (29 samples), the microbiota comprised 72,41% (21 samples) of Actinobacillus actinomycetemcomitans, only 17,25% (5 samples) of Porphyromonas gingivalis and 24,14% (7 samples) of Prevotella intermedia. The Qui-Square test revealed no statistically significant qualitative differences for the two groups analyzed and the results indicated that probably the crestal bone changes around titanium implants with 2-piece configuration are dependent of a mechanical factor.